Efeito da adição de plasma seminal e de sua composição bioquimica sobre os espermatozóides epididimários de caprinos - Silva, Katiane Queiroz da (2009)
The objective of this study was to verify the effect of the addition and of the composition of the seminal plasma (SP) on the characteristics of the epididymal spermatozoa (ES) of goat. Eight goat males were used for obtaining of the biological material so that, the SP it was obtained in previous collections and stored at -18 oC until that proceeded to the addition to ES and the biochemical analyses. ES were obtained of the tail of the epididymal by the method of surgical castration. Four sample of 100 μL were removed from the "pool" of ES, and in two of them 120 μL were added of SP. Two sample, one with and other without SP, were diluted in a concentration of 200 x 106 sptz /mL, in the extender citrate-yolk (CY) and in the extender tris-yolk (TY). The samples were evaluated the vigor, motility and motility degradation rate (TDM) in fresh state and for the test of slow thermoresistence, after two and 24 hours of conservation. For the determination of fructose levels and total proteins were used specific kits of In Vitro Diagnóstico S/A®. The determination of activity of the phospholipase A2 was realized by the technique of the pH-stat. For the analysis of the data was used the statistical program SAS@. The results demonstrated that the addition of SP to ES reduced seminal parameters significantly, except in the extender TY when the animals were to grouped in function of concentration of total proteins of SP. Besides, the TY, when used to conserve the ES added of SP with low fructose concentration (540 mg/dL) preserved the seminal characteristics better. It follows that the initial concentration of fructose in the seminal plasma influenced the quality of conservation of the epididymal spermatozoa; as for the total proteins just affected the conservation in the citrate-yolk and the intensity of activity of the phospholipase A2 did not interfere in the conservation at 5 ºC of the epididymal spermatozoa of goat